Recent advances in the development of poly(ester amide)s-based carriers for drug delivery - Rui Xie; Jiang Li; Min Zhao; Fan Wu (Elsevier, 2024)
Biodegradable and biocompatible biomaterials have several important applications in drug delivery. The biomaterial family known as poly(ester amide)s (PEAs) has garnered considerable interest because it exhibits the benefits of both polyester and polyamide, as well as production from readily available raw ingredients and sophisticated synthesis techniques. Specifically, α-amino acid-based PEAs (AA-PEAs) are promising carriers because of their structural flexibility, biocompatibility, and biodegradability. Herein, we summarize the latest applications of PEAs in drug delivery systems, including antitumor, gene therapy, and protein drugs, and discuss the prospects of drug delivery based on PEAs, which provides a reference for designing safe and efficient drug delivery carriers.